Pea Seedling Histaminase as a Novel Therapeutic Approach to Anaphylactic and Inflammatory Disorders - Emanuela Masini; Danielle Bani; Cosimo Marzocca; Mircea Alexandru Mateescu; Pier Francesco Mannaioni; Rodolfo Federico; Bruno Mondovì (The Scientific World Journal)
Amine oxidases (AOs) are ubiquitous enzymes involved in the metabolism of biogenic amines. Copper AOs (Cu-AOs) catalyze the oxidative deamination of primary amine groups of several biogenic amines, such as putrescine, cadaverine, and histamine. In the present review, the effects of a plant amine oxidase (Cu-AO, histaminase, EC1.4.3.6) purified from pea seedlings in the modulation of IgE-mediated allergic reactions, and in the prevention of cardiac and splachnic postischemic reperfusion damage are reported.